Rosa Zone : die schwul-lesbische Zeitung für Nordrhein-Westfalen. (Dortmund : Rosa Zone Verlag.)
Fonds Suzan Daniel (FSD)
Periodiciteit: maandelijks
Redactie: Beurhausstrasse 58, 44137 Dortmund
Duits
Periodiek